Myocardial intramural course may reduce left ventricular ejection fraction of patients suffering from coronary heart disease - Miaomiao, Shi; Jiaqi, Zheng; Xiaomeng, Li; Shanshan, Li; Jie, Wang; Kaicheng, Liu; Mei, Jia; Ming, Su (Frontiers in Cardiovascular Medicine, 2025)
BackgroundMyocardial intramural course (MIC), a benign anatomical lesion, is an abnormal anatomical structure formed due to abnormal blood vessel routing. An increasing number of studies indicate that MIC is associated with coronary heart disease (CHD). However, it remains unclear whether MIC contributes to cardiac function impairment in patients with CHD. Thus, this study is to observe the association between MIC and cardiac function in patients with CHD.MethodsAll participants were recruited from the Department of Cardiology, Peking University People's Hospital from August 2022 to September 2023. A total of 126 patients were diagnosed with MIC by coronary angiography and/or coronary CT angiography. Among them, a total of 39 patients diagnosed with MIC and CHD were enrolled in the MIC-CHD group. Sixty cases of monthly stratified CHD patients were randomly selected, into the CHD group as controls.ResultsThe left ventricular ejection fraction (LVEF) of patients in the MIC-CHD group was lower than that in the CHD group (0.62 vs. 0.67, p = 0.0153). LVEF in patients of MIC-CHD was negatively correlated with the systolic stenosis degree of mural coronary artery (MCA) (r = −0.6474, p = 0.0123) and MIC length (r = −0.5712, p = 0.0414).ConclusionsThe combination of MIC in patients with CHD may contribute to the reduction of LVEF, whereas MIC length and the systolic stenosis degree of MCA were negatively correlated with LVEF.